Kemampuan Pemecahan Masalah Sosial Siswa Kelas 12 SMA Negeri 1 Ciruas - Rahmawati Rahmawati; Ahmad Baehaqi; Yunisa Prestisia Murtidewi; Yesha Rahmadita; Mirnawati Mirnawati; Alifah Salsabila; Wafiq Azizah; Yolinda Evinalisa; Vanesha Amanda Fritania; Rizky Amelia; Ehan Fuazan Rahmatillah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
The purpose of this research is to measure the performance of 12th grade students at SMA Negeri 1 Ciruas in the subject of biodiversity and to assess the 12th grade students ability to solve problems through environmentally based learning activities. The research procedure involves using pre-tests and post-tests. The pre-test is used to determine the students initial abilities. The post-test is conducted to assess the students problem solving abilities after learning through Problem Based Learning using Student Discussion Sheets (LKPD). Student performance data, obtained from answering Student Discussion Sheets (LKPD), is analyzed descriptively and qualitatively. Scores obtained from all assessed aspects are then converted to determine the groups assessment criteria. The problem solving abilities of 12th grade students at SMA Negeri Ciruas fall into the "Good" category, and there is an improvement in scores between the pre-test and post-test evaluations.